No momentum in the world economy - Günter Großer; Günter Weinert (Intereconomics, 1996)
The upswing in the world economy has lost momentum surprisingly fast. A slowdown in growth in North America had been expected, but the budding hopes in Japan and Western Europe for a continued recovery in utilisation of capacity and employment were disappointed. Are there grounds for such hopes in 1996 or have the structural constraints on growth now become so powerful as to prevent a more significant economic revival?
Keywords: 330; Economic Trends